Avaliação da gestão das empresas construtoras de pequeno e médio porte de Curitiba quanto ao nível de aderência às práticas de gestão do conhecimento - Staidel, Gizele Pires (2019)
The construction industry is of great importance in the national scenario considering the Brazilian Gross Domestic Product (GDP) and employment and income data. Systematic use of people's knowledge may be an alternative to gain competitive advantage from organizations, but it can often be overlooked by small and mediumsized enterprises (SMEs) for lack of awareness of KM practices. The general objective of this research was to evaluate the management of Curitiba's small and medium-sized construction companies regarding the level of adherence to the Knowledge Management (KM) practices by conducting a diagnosis according to the model proposed in the European Guide to Good Management Practice. Knowledge This guide sets out 5 knowledge activities, namely: identification, creation, storage, sharing and use. Initially, a bibliometric analysis on the subject was performed and a questionnaire was applied to construction companies in Curitiba for data collection. With the obtained data, the adherence level obtained in this study was compared with similar studies in other areas that used the model proposed by Bukowitz and Williams (2002). This study obtained 31.1% adherence to the responses totally agree and 72.4% of adherence adding the answers totally agree and partially agree. The strengths of the five knowledge activities are sharing and use. It was also evaluated the convergence between the vision of the company management and the view of employees in relation to KM and at the end of the analysis, it can be stated that although there are divergences in some points, in the final evaluation there is convergence between the answers. Comparing the results of this study with other studies that used the methodology proposed by Bukowitz and Williams (2002), considering only the tactical process, it was noticed an average adherence, 6.7% higher obtained by the construction companies. Considering the overall average, including the strategic process, the difference was even greater, with a difference of 9.3%. In both methodologies, the overall average obtained is above other studies by Bukowitz and Williams (2002) which state that in general, the companies' adherence level is approximately 55%. It can be concluded that the results were higher than expected, since 78% of the companies that answered the questionnaire have PBQPH / ISO 9001 certification, favoring the positive result.